Impact of digital economy on enterprise innovation in China: Evidence from a panel data set of Chinese companies - Long, Yunfei; Sutunyarak, Chonlavit (Asian Journal of Economic Modelling, 2025)
As a new driving force for high-quality development, the digital economy is reshaping knowledge diffusion and corporate innovation models, becoming a key force in optimizing resource allocation, improving operational efficiency, and driving innovation. This paper uses data from a sample of 30,391 Chinese enterprises from 2015 to 2022, employing a two-way fixed-effects model and a mediation effect model to empirically examine the impact of the development of the digital economy on innovation in Chinese enterprises. The results show that the digital economy significantly increases patent applications, confirming its role as a catalyst for corporate innovation. Mechanism analysis suggests that R&D investment plays a mediating role of approximately 20%, highlighting its importance in transforming digitalization into innovative outcomes. Heterogeneity analysis further demonstrates that this effect is more pronounced in non-state-owned enterprises. At the industry level, health and social work, wholesale and retail, and manufacturing benefited the most, while real estate and construction were negatively impacted. The contributions of this study are: first, it expands the empirical research on the relationship between the digital economy and innovation, providing a new perspective for digital empowerment of innovation; second, it identifies R&D investment as a significant mediating mechanism, deepening our understanding of the innovation-driven mechanism; third, through heterogeneity analysis, it highlights industry and ownership differences, providing a reference for differentiated policy making.